2021
DOI: 10.1177/22125868211007011
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic’s disruption on university teaching and learning and competence cultivation: Student evaluation of online learning experiences in Hong Kong

Abstract: The COVID-19 pandemic outbreak has forced online teaching and learning to be the primary instruction format in higher education globally. One of the worrying concerns about online learning is whether this method is effective, specifically when compared to face-to-face classes. This descriptive quantitative study investigates how students in higher education institutions in Hong Kong evaluated their online learning experiences during the pandemic, including the factors influencing their digital learning experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 61 publications
3
58
0
4
Order By: Relevance
“…A study conducted by Mok et al (2021) that evaluates online learning experiences of students in higher education institutions in Hong Kong during the pandemic, found that students were dissatisfied with emergency online learning. So addressing the challenges of emergency online learning, higher education institutes management should find a mixed-mode of delivery for enhancing teaching and learning.…”
Section: Background Perspectivementioning
confidence: 99%
“…A study conducted by Mok et al (2021) that evaluates online learning experiences of students in higher education institutions in Hong Kong during the pandemic, found that students were dissatisfied with emergency online learning. So addressing the challenges of emergency online learning, higher education institutes management should find a mixed-mode of delivery for enhancing teaching and learning.…”
Section: Background Perspectivementioning
confidence: 99%
“…As some participants expressed, stress factor during the pandemic has motivated some students to take the easy way out. Studies from Bangladesh (Khan, et al 2021), Hong Kong (Mok, et al 2021), and Vietnam (Tran, et al 2021) also found that students mentally and psychologically struggled during the pandemic, and some showed signs of depression; they did not find online learning satisfying; they lacked the computer skills and sometimes the equipment to complete online assignments.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid growth in distance learning became more prominent when the COVID-19 crisis started in 2020, which has now become the most significant challenge for many educational institutions (Daniel, 2020). The pandemic has forced online teaching and learning to become the primary instruction medium at various levels of education (Butnaru, 2021;Mok, 2021). Governments were forced to shut down schools, which were required to switch to distance education and online learning, even without any adequate preparation.…”
Section: Introductionmentioning
confidence: 99%